Underworld - Rosenberg, Tom.; Lucchesi, Gary.; Wright, Richard; McBride, Danny; Wiseman, Len.; Beckinsale, Kate.; Speedman, Scott; Sheen, Michael; Brolly, Shane; Nighy, Bill, 1949-; Leder, Erwin; Myles, Sophia, 1980-; et al. (Culver City, Calif. : Columbia TriStar Home Entertainment, 2004)
A war has been raging between the Vampires and the Lycans for centuries. Selene is a vampire Death Dealer who finds out that the Lycans have plans to capture Michael. As Selene begins to track Michael, she becomes more convinced that the Lycans are planning an attack against the Death Dealers. The vampire kingpin, Kraven, is certain the Lycans do not have that kind of intelligence. As Selene shadows Michael, she finds herself wanting to protect him, but when he's attacked by Lucian, the leader of the werewolf community, and the man she wants to save has now become a sworn enemy.
Originally released as a motion picture in 2003.
Special features: director and writer commentary; technical effects; creature features; stunts featurette; sights and sounds of "Underworld"; the making of "Underworld"; finch "Worms and Earth"; storyboard comparison; TV spots; theatrical trailers.
Kate Beckinsale, Scott Speedman, Michael Sheen, Shane Brolly, Billy Nighy, Erwin Leder, Sophia Myles, Robbie Gee, Wentworth Miller.
DVD; Dolby Digital, DTS, SDDS.
Keywords: Vampires; Werewolves; Feature films; Vampire films; Video recordings for the hearing impaired